Explore the Rights of Journalists in the Imāmiyaah Jurisprudence - Hussein Saberi; H. Haqiqatpour (آموزه‌‌های فقه مدني)
Given to the age of communication and the need for jurisprudence to answer the issues of community, exploring the rights of journalists is very important. Looking at the present Islamic Republic of Iran press law, this paper considers and analyzes jurisprudentially the journalists’ rights such as freedom of information, safety and criminal immunity. It has been proved in this paper that for the realization of Islamic information, these cases are the minimum requirements and there is much distance to achieve the religious media.